2020
DOI: 10.1080/02188791.2020.1717436
|View full text |Cite
|
Sign up to set email alerts
|

Active learning engagement in teacher preparation programmes - A comparative study from Qatar, Lebanon and China

Abstract: This study investigated student teachers' preferred active learning strategies, and those which they actually received during their teacher preparation programmes. An explanatory mixed methods research design was adopted, including a survey completed by 308 participants and group interviews involving 38 participants. Data were gathered from student teachers completing their university education in three countries: Qatar, Lebanon, and China. Results indicated the prevalence of and a preference for a passive mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…However, they may be highly related to the sociocultural context of student engagement within the institution (Kahu, 2013), which can be seen as a limitation to implementing PBL at the course level (Kolmos, 2017;Strobel & van Barneveld, 2009). The factor of team dynamics can also be problematic since training for collaborative learning demands time and institutional supports (Borrego, Karlin, McNair, & Beddoes, 2013), particularly in a socio-cultural context where students are not used to it (Du, Kolmos, Ahmed, Spliid, Lyngdorf, & Ruan, 2020;Du, Chaaban, Sabah, Al-Thani, & Wang, 2020). In sum, all three factors this study identified can both support and constrain student engagement in PBL, and they can also be related to the history and tradition of the Arabic educational culture (Du, Ebead, Sabah, Ma, & Naji, 2019;Du, Naji, Sabah, & Ebead, 2020;Sabah & Du, 2018).…”
Section: Discussion Student Engagement In Pbl and Supporting And Consmentioning
confidence: 99%
“…However, they may be highly related to the sociocultural context of student engagement within the institution (Kahu, 2013), which can be seen as a limitation to implementing PBL at the course level (Kolmos, 2017;Strobel & van Barneveld, 2009). The factor of team dynamics can also be problematic since training for collaborative learning demands time and institutional supports (Borrego, Karlin, McNair, & Beddoes, 2013), particularly in a socio-cultural context where students are not used to it (Du, Kolmos, Ahmed, Spliid, Lyngdorf, & Ruan, 2020;Du, Chaaban, Sabah, Al-Thani, & Wang, 2020). In sum, all three factors this study identified can both support and constrain student engagement in PBL, and they can also be related to the history and tradition of the Arabic educational culture (Du, Ebead, Sabah, Ma, & Naji, 2019;Du, Naji, Sabah, & Ebead, 2020;Sabah & Du, 2018).…”
Section: Discussion Student Engagement In Pbl and Supporting And Consmentioning
confidence: 99%
“…From the institutional perspective, Digital learning orientation adequate efforts should be made to facilitate infrastructural facilities for both students and educators. Institutional culture should ensure effective communication that helps students comprehend the necessity and prospective benefits of the change (Du et al, 2020).…”
Section: Digital Learning Orientationmentioning
confidence: 99%
“…Accepting change can improve the chances of successfully implementing the change and maximizing change effectiveness (Bouckenooghe et al, 2009). In addition, they should accept the change as an appropriate way to achieve the educational objectives in the given context and be agentic and proactive in the change to develop professional competencies (Du, Chaaban, Sabah, Al-Thani, & Wang, 2020). If students are given sufficient explanation that the change is needed, they are more likely to develop motivation and positive attitudes and establish trust and peer support in their environment (Hsu et al, 2012;Martin, Ahlgrimelzell & Budhrani, 2017;Mayer, 2014).…”
Section: Initial Preparedness and Motivation For Online Learningmentioning
confidence: 99%
“…Implementing change is highly contextual, and accordingly, support from the environment is needed Du, Chaaban, Sabah, Al-Thani, & Wang, 2020). Leadership support is key to improving motivation and self-efficacy to ensure the success of change efforts (Holt & Vardaman, 2013).…”
Section: Supportmentioning
confidence: 99%